Assessment of Marketability of Tourism Management and Hospitality Programs of the Select Private College - Pabelona, Rechie B.; P. Alcantara, Elyn Mae (International Journal of Scientific Research and Management (IJSRM), 2023)
The study aimed to assess the status of Tourism Management and Hospitality programs of the Select Private College in Negros Occidental in relation to the 7 P’s of marketing mix elements namely: product, price, place, promotion, people, process, and physical evidence. The research also sought to identify the strengths, weaknesses, opportunities, and threats through SWOT analysis and the problems and issues encountered by Tourism Management and Hospitality Programs of the institution. To meet the research objectives, 265 students taking BS Tourism Management, Diploma in Travel & Tours Management, Diploma in Hotel & Restaurant Management, and Diploma in Culinary Arts programs were used as participants of the study. The descriptive survey research design was employed in gathering the data, which was collected from a self-made survey questionnaire. The statistical applications used in analyzing the data were the mean, frequency and percentage. It is concluded in this study that students assessed the current status of Tourism Management and Hospitality programs with regards to the 7 P’s of marketing mix elements as fair and so the researcher find necessary actions and strategies to work on with the improvement of all the elements. Also, the SWOT analysis conducted reveals that there are more strength in the school than its weaknesses and more opportunities than threats.